Peran Orang Tua dalam Mengembangkan Komunikasi Siswa Sekolah Dasar pada Pembelajaran Daring - Arif Trimuktiyadi; Aziza Lukmitasari; Novita Indriyani; Vila Suvia Ramadzani (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2022)
The study aims to describe the role of parents and to determine the factors which influence the development of students’ communication skills in grade four at one of the public elementary schools in Kutoarjo during online learning. The research method used a qualitative approach with a case study research type. The subjects of this study were 3 parents, 3 students, and a teacher of SDN 1 Kutarjo who conducted online learning during the pandemic. Data collection techniques include interviews and observation. In analyzing data used Milles, Huberman, and Saldana model which consists of data collection, data display, and conclusion. The results showed that (1) the role of parents in students’ communication development online learning includes openness, empathy, supportiveness, positiveness, and equality; (2) parents supporting factors in developing students, communication skills in grade four of SDN 1 Kutoarjo during online learning are communicator’s messages, creation of a message, understanding of the message, relationships of the message, and feedback. Meanwhile, the inhibiting factor is the parents’ busyness. Through the implementation of parents’ attitude in giving guidance on effective communication to students, it can assist students in developing communication skills in online learning. Keywords: the role of parents, communication, online learning, elementary school ===================================================== Riset ini bertujuan untuk menganalisis peran orang tua serta dapat mengetahui faktor yang memengaruhi dalam pengembangan komunikasi siswa kelas IV di salah satu sekolah negeri dasar Kutoarjo selama pembelajaran daring. Metode riset memanfaatkan pendekatan kualitatif dengan jenis penelitian studi kasus. Subjek dalam riset ini ialah 3 orang tua, 3 siswa, dan 1 guru yang menjalankan pembelajaran di rumah bagi anak-anak sekolah dasar pada masa pandemi. Teknik pengumpulan data yang mencakup wawancara serta pengamatan. Dalam menganalisis data mengggunakan model Milles dan Huberman yaitu pengumpulan data, penyajian data, dan penarikan kesimpulan. Hasil analisis memperlihatkan bahwasanya (1) peran orang tua dalam perkembangan komunikasi siswa selama pembelajaran daring yaitu keterbukaan (openness), empati (empathy), sikap mendukung (supportiveness), sikap positif (positiveness), dan kesetaraan (equality); (2) faktor pendukung orang tua dalam mengembangkan komunikasi siswa kelas IV SD selama pembelajaran daring yakni pesan komunikator, pembuatan pesan, pemahaman pesan, hubungan pesan, serta umpan balik sedangkan faktor penghambat yaitu kesibukan orang tua. Melalui sikap yang diterapkan orang tua dalam memberikan bimbingan komunikasi yang efektif kepada siswa mampu membantu siswa dalam mengembangkan komunikasinya dalam pembelajaran daring. Kata kunci: peran orang tua, komunikasi, pembelajaran daring, sekolah dasar